Lipid Raft Phase Modulation by Membrane-Anchored Proteins with Inherent Phase Separation Properties - Lee, Il-Hyung (ACS Omega, 2019)
[Image: see text] Cell plasma membranes are a heterogeneous mixture of lipids and membrane proteins. The importance of heterogeneous lipid domains (also called lipid rafts) as a molecular sorting platform has been implicated in many physiological processes. Cell plasma membranes that are detached from the cytoskeletal structure spontaneously phase separate into distinct domains at equilibrium, which show their inherent demixing properties. Recently, researchers have discovered that proteins with strong interprotein interactions also spontaneously phase separate into distinct protein domains, thus enabling the maintenance of many membraneless organelles. Protein phase separation may also take place on the lipid membranes via lipid-anchored proteins, which suggests another potential molecular sorting platform for physiological processes on the cell membrane. When two-phase separation properties coexist physiologically, they may change the resulting phase behavior or serve as independent sorting platforms. In this paper, we used in vitro reconstitution and fluorescence imaging to systematically quantify the phase behavior that arises when proteins with inherent phase separation properties interact with raft mixture lipid membranes. Our observations and simulations show both that the proteins may enhance lipid phase separation and that this is a general property of phase-separating protein systems with a diverse number of components involved. This suggests that we should consider the overall effect of the properties of both membrane-anchored proteins and lipids when interpreting molecular sorting phenomena on the membranes.